Pengaruh Penggunaan Lagu-Lagu Anak Dalam Meningkatkan Kosakata Bahasa Arab Siswa Mi Cibanoang - mu'arif, salmanabdullah; Syahra, RikaMauladi; Saputro, Setyo; Hadi, RifanNur; Mardani, Dadan (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research explores the impact of utilizing children's songs as a teaching medium to enhance Arabic vocabulary acquisition among MI Cibanoang students. The study employs a qualitative approach with a case study design, involving classroom observations, teacher interviews, and document analysis. Results reveal that songs significantly improve vocabulary retention, especially when accompanied by physical activities and context-based explanations. However, effectiveness varies by grade level, with younger students requiring more support to grasp meanings. The findings highlight the necessity of adapting songs to students’ needs and integrating them with other learning methods. This study contributes to the development of innovative Arabic teaching strategies, fostering engaging and meaningful learning experiences.